Karakterisasi Fisik Pati Tapioka Modifikasi Gabungan Hidroksipropilasi dengan Fosfat-Ikat Silang - Didah Nur Faridah; Ali Thonthowi (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2020)
Native tapioca starch has a weakness in its functional properties which causes limited use of starch as a food ingredient. This weakness can be overcome by applied double modifications with hydroxypropylation and cross-linking processes. The hydroxypropylation was applied using various concentrations of propylene oxide (8, 10, and 12%), then followed by crosslinking modifications using a combination of STPP (Sodium tripolyphosphate) and STMP (sodium phosphate) with a ratio of 2%: 5%. The results of the double modification can changed the physical and chemical characteristics of starch. These changes include the gelatinization temperature of modified tapioca starch (66.00 – 68.00 oC) which is lower than the natural starch (68.45 oC). The peak viscosity of modified tapioca starch (> 5735 cP) was higher than the original starch (5635 cP) with the viscosity setback was also higher (3136-3564 cP) than the original starch (1192 cP). Modified starch has a lower viscosity decrease value (698-1530 cP) than the original starch (4089 cP). Double modified tapioca starch has heat-resistant and stirring properties